Untimely Matter in the Time of Shakespeare - Harris, Jonathan Gil (University of Pennsylvania Press, Inc, 2011)
Selected byChoicemagazine as an Outstanding Academic Title for 2009 The New Historicism of the 1980s and early 1990s was preoccupied with the fashioning of early modern subjects. But, Jonathan Gil Harris notes, the pronounced tendency now is to engage with objects. From textiles to stage beards to furniture, objects are read by literary critics as closely as literature used to be. For a growing number of Renaissance and Shakespeare scholars, the play is no longer the thing: the thing is the thing. Curiously, the current wave of "thing studies" has largely avoided posing questions of time. How do we understand time through a thing? What is the time of a thing? InUntimely Matter in the Time of Shakespeare, Harris challenges the ways we conventionally understand physical objects and their relation to history. Turning to Renaissance theories of matter, Harris considers the profound untimeliness of things, focusing particularly on Shakespeare's stage materials. He reveals that many "Renaissance" objects were actually survivals from an older time-the medieval monastic properties that, post-Reformation, were recycled as stage props in the public playhouses, or the old Roman walls of London, still visible in Shakespeare's time. Then, as now, old objects were inherited, recycled, repurposed; they were polytemporal or palimpsested. By treating matter as dynamic and temporally hybrid, Harris addresses objects in their futurity, not just in their encapsulation of the past.Untimely Matter in the Time of Shakespeareis a bold study that puts thematériel-the explosive, world-changing potential-back into a "material culture" that has been too often understood as inert stuff.